(untitled) (Swiss Medical Weekly, 2014)
Switzerland, the country with the highest health expenditure per capita, is lacking data on trauma care and system planning. Recently, 12 trauma centres were designated to be reassessed through a future national trauma registry by 2015. Lausanne University Hospital launched the first Swiss trauma registry in 2008, which contains the largest database on trauma activity nationwide. METHODS: Prospective analysis of data from consecutively admitted shock room patients from 1 January 2008 to 31 December 2012. Shock room admission is based on physiology and mechanism of injury, assessed by prehospital physicians. Management follows a surgeon-led multidisciplinary approach. Injuries are coded by Association for the Advancement of Automotive Medicine (AAAM) certified coders. RESULTS: Over the 5 years, 1,599 trauma patients were admitted, predominantly males with a median age of 41.4 years and median injury severity score (ISS) of 13. Rate of ISS >15 was 42%. Principal mechanisms of injury were road traffic (40.4%) and falls (34.4%), with 91.5% blunt trauma. Principal patterns were brain (64.4%), chest (59.8%) and extremity/pelvic girdle (52.9%) injuries. Severe (abbreviated injury scale [AIS] score ≥3) orthopaedic injuries, defined as extremity and spine injuries together, accounted for 67.1%. Overall, 29.1% underwent immediate intervention, mainly by orthopaedics (27.3%), neurosurgeons (26.3 %) and visceral surgeons (13.9%); 43.8% underwent a surgical intervention within the first 24 hours and 59.1% during their hospitalisation. In-hospital mortality for patients with ISS >15 was 26.2%. CONCLUSION: This is the first 5-year report on trauma in Switzerland. Trauma workload was similar to other European countries. Despite high levels of healthcare, mortality exceeds published rates by >50%. Regardless of the importance of a multidisciplinary approach, trauma remains a surgical disease and needs dedicated surgical resources.